Effectiveness and use of prophylactic antibiotics in elective and emergency caesarean section at tertiary care hospital - Lingam, K. Rama; Ramineni, Hari Babu; Firdous, Shaik Gulshan; Yamuna, P.; Madhuri, B.; Chidrupi, D. N. S. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Post-operative infections in obstetrics and gynecological settings have been higher compared to other specialties. Women undergoing caesarean section have 5 to 20-fold greater risk for infection compared with vaginal delivery. Many studies reported antimicrobial prophylaxis prevent post-operative infections. Hence this study concentrates the evaluation of the prescribing antimicrobial use and to assess the frequency of post-operative morbidity related to infection in subjects undergoing caesarean section. The aim of the study was to analysis the effectiveness, prophylactic antibiotics (amoxicillin versus ceftriaxone) and to evaluate the post-operative (caesarean) infections in patients undergoing lower segment caesarean section (elective and emergency). Methods: This is a prospective observational study which assessed the effectiveness and use of prophylactic antibiotics in patients undergoing cesarean section at department of obstetrics and gynecology. The study was conducted over a period of one year. Results: The corresponding mean age of all the study population in amoxicillin group (n=113) was 56.5±28.5 and in ceftriaxone group (n=97) was 48.5±26.5 respectively. The participant who underwent previous cesarean section in amoxicillin group is 65.48% similarly in ceftriaxone group is 47.42%. The patients with fetal distress in ceftriaxone group are 14.77% and in amoxicillin group is 8.92%. Failed induction in amoxicillin group is 9.82% and in ceftriaxone group is 6.81%. The number of days in hospital stay in amoxicillin group is 42.42% and in ceftriaxone group is 45.94%. The post-operative complications in amoxicillin group reported, with Febrile Illness are 40% and wound Infection is 60%. Conclusions: Administration of pre-operative antibiotics significantly reduce post-operative infections. Use of ceftriaxone as a prophylactic antibiotic in patients undergoing lower segment caesarean section (elective and emergency) is more effective than Amoxicillin in preventing post-operative infections.